Hubungan sosio demografi dan pendapatan dengan kepatuhan membayar iuran PBPU pekerja mandiri di BPJS kesehatan KC Jambi - Arnild Augina Mekarisce; Dwi Noerjoedianto; Adila Solida (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2022)
Abstract Background : Payment of BPJS Health contributions to PBPU-independent workers is a major challenge for BPJS Health, because there is no agency responsible for consistent payment of contributions to these participants. High levels of non-compliance with payment of contributions can reduce the collectability of contributions and pose a significant financial risk to BPJS Kesehatan. Nationally, the highest arrears of participant contributions were PBPU participants-independent workers (Rp. 5,654,930,976,944,-), which was 86.88% of the total arrears of contributions for BPJS Health participants. Meanwhile, the arrears of participant contributions in the BPJS Kesehatan Jambi Branch Office as of December 4, 2020 were around 215,369 people with a total of Rp. 161,513,573,648,-. The purpose of this study was to identify the relationship between sociodemographic factors and compliance with paying BPJS Health contributions to PBPU participants-Independent Workers in the Jambi Branch Office working area. Method : This study is a descriptive study using a cross-sectional design. The research population is PBPU participants- BPJS Health independent workers in the Jambi Branch Office working area. The sample calculation uses the Lemeshow formula, which is as many as 192 samples. The research instrument used a questionnaire, while data processing was done by editing data, data coding, data entry, data cleaning, and data processing, then analyzed univariate and bivariate with chi-square test. Results : The results showed that there was a significant relationship between income and compliance with paying BPJS Health contributions (p-value = 0.045) and there was no significant relationship between age (p-value = 0.120), gender (p-value = 0.705) , education (p-value=0.089), and number of family members (p-value=0.051) with compliance in paying BPJS Health contributions to PBPU participants-independent workers in the Jambi Branch Office working area. Conclusion : There is a relationship between income and compliance with paying contributions, and there is no relationship between age, gender, education, and number of family members with compliance with paying BPJS Health contributions to PBPU participants-independent workers in the Jambi Branch Office working area. BPJS Kesehatan is expected to be able to profile and switch contributions for BPJS Health participants and prospective participants, especially for PBPU-independent workers. Keywords : contributions, PBPU-Independent Workers, Compliance.